2022
DOI: 10.21580/pjpp.v7i1.10606
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness, gratitude, and the flourishing of emerging adults with divorced parents

Abstract: Parental divorce affects the ability of individuals to flourish. This study aims to determine the relationship between forgiveness and gratitude and the flourishing of emerging adults whose parents have divorced. Voluntary convenience sampling was used to identify respondents (N = 429 emerging adults whose parents had been divorced for at least two years). Data were collected using the Emotional Forgiveness Scale, the Gratitude Questionnaire-Six Item Form, and the PERMA Profiler. Data analysis was performed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Research conducted by Tessy et al (2022), which examined the correlation between gratitude and forgiveness on flourishing, also strengthens the results of this study that gratitude affects the flourishing rate and has a greater contribution to increasing flourishing than other criterion variables, namely forgiveness. Another study that corroborated the results revealed that gratitude influenced flourishing by 27% with adjustments to disability as a moderator variable (Phillips et al, (2022).…”
Section: Variablesupporting
confidence: 79%
See 1 more Smart Citation
“…Research conducted by Tessy et al (2022), which examined the correlation between gratitude and forgiveness on flourishing, also strengthens the results of this study that gratitude affects the flourishing rate and has a greater contribution to increasing flourishing than other criterion variables, namely forgiveness. Another study that corroborated the results revealed that gratitude influenced flourishing by 27% with adjustments to disability as a moderator variable (Phillips et al, (2022).…”
Section: Variablesupporting
confidence: 79%
“…The role of gratitude in flourishing is evidenced by research conducted by Tessy et al, which shows that gratitude contributes to the flourishing rate of young adults with divorced parents (Tessy et al, 2022). Other similar studies have also proven that gratitude affects new college students' well-being (Daulay et al, 2022).…”
Section: Introductionmentioning
confidence: 91%
“…Communication within the family and religiosity contribute to increasing family resilience (Latifa et al, 2020). Forgiveness and gratitude have been proven to predict the flourishing level in the context of emerging adulthood (Tessy et al, 2022). In facing the COVID-19 pandemic, togetherness and partnership between husband and wife are the essential factors for a resilient millennial family (Kasdi & Saifudin, 2020).…”
Section: Dynamics Of a Flourishing Muslim Familymentioning
confidence: 99%
“…Ada beberapa alasan orang bercerai, seperti alasan perceraian pada umumnya yaitu karena sudah tidak cocok satu sama lainnhya, salah satu pihak selingkuh dan suami tidak memberi nafkah (lahir dan batin) dalam jangka waktu lama. Oleh karena itu adanya perceraian sepasang suami dan istri serta tidak menutup kemungkinan menjadi dasar munculnya permasalahan yang dialami oleh anaknya ketika setelah terjadinya perceraian yang dilakukan oleh kedua orangtua nya tersebut (Tessy et al, 2022).…”
Section: Pendahuluanunclassified